(untitled) (Movimenta (ISSN 1984-4298), 2026)
Simultaneous use of medicines and food can interfere with the kinetics of the medicines, and absorption and utilization of nutrients. Analyzed the information on medicine-food interactions in package leaflets and whether there is agreement between this information and the literature. The electronic package leaflets of medicines listed on the National List of Essential Medicines (RENAME) were analyzed. A comparative analysis was carried out between the information contained in the literature and in the leaflets intended for health professionals and patients. Of the 110 medicines, 65 (59.1%) had some interaction with food. When comparing the information in the literature with the health professional’s leaflets, there was agreement in the information in 6 (9.2%), partial agreement in 22 (33.8%), no agreement in 22 (33.8%) and data non-existent in 15 (23.1 %) of the professional’s leaflets. In relation to patient’s package leaflets, there was agreement in 6 (9.2%), partial agreement in 19 (29.2%), no agreement in 17 (26.2%) and lack of data in 23 (35.4%). Pharmacokinetic interactions were the most common. There was a high frequency of absence of relevant information on medicine-food interaction in medicine leaflets, and this can lead to greater exposure to risks related the rational use of medicines.